2019
DOI: 10.3174/ajnr.a6075
|View full text |Cite
|
Sign up to set email alerts
|

Texture Analysis in Cerebral Gliomas: A Review of the Literature

Abstract: Texture analysis is a continuously evolving, noninvasive radiomics technique to quantify macroscopic tissue heterogeneity indirectly linked to microscopic tissue heterogeneity beyond human visual perception. In recent years, systemic oncologic applications of texture analysis have been increasingly explored. Here we discuss the basic concepts and methodologies of texture analysis, along with a review of various MR imaging texture analysis applications in glioma imaging. We also discuss MR imaging texture analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
86
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(88 citation statements)
references
References 75 publications
0
86
1
1
Order By: Relevance
“…The earliest reports have indicated that TA based on CT images has the potential of differential diagnosis of tumour heterogeneity 19 20. To date, there have been some reports on glioma grading using MRI TA 21. However, the results have been inconclusive.…”
Section: Discussionmentioning
confidence: 99%
“…The earliest reports have indicated that TA based on CT images has the potential of differential diagnosis of tumour heterogeneity 19 20. To date, there have been some reports on glioma grading using MRI TA 21. However, the results have been inconclusive.…”
Section: Discussionmentioning
confidence: 99%
“…Table 1 [41], reflecting texture/spatial arrangements of pixel intensities present in the ROI [42]. Two-dimensional (2D) GLCM is usually quantified in 4 directions (0°, 45°, 90°, and 135°) and three-dimensional (3D) GLCM in 13 directions [43]. GLCM features are further defined in Table 2.…”
Section: Types Of Tamentioning
confidence: 99%
“…GLRLM features are described in Table 3. GLCM and GLRLM provide fine texture in short distance and run, and provide coarse texture in longer distance and run [43]. The coarseness of texture is related to spatial frequency.…”
Section: Types Of Tamentioning
confidence: 99%
“…This data are also sought to predict clinical outcomes, such as patients' survival and responses to therapy (7). The features commonly included in this type of analysis are: volume, shape, intensity (MRI signal) and other texture features, referring to pixel intensities, their distribution pattern, and their interrelationships (20). Nowadays, the radiomics analysis has been used for various types of cancer including lung cancer (21)(22)(23) and prostate cancer (24)(25)(26)).…”
Section: Introductionmentioning
confidence: 99%